Gamma shaped monopole patch antenna for tablet PC - Islam, Md Rafiqul; Habib, Mohammad Shawkat; Abdullah, Khaizuran (arpnjpurnals.com, 2015)
With the increasing demand of using multiple services in a single device, instead of using multiple antennas, current trend is to use single antenna capable of communicating in multiple frequency bands. For the devices like tablet PC, the need of accommodating the physical infrastructure through single multiband antenna is greatly useful. For the multiband operation, a gamma shaped structure is proposed for tablet PC. Gamma shaped monopole structure is designed and simulated using the Computer Simulation Technology (CST) Microwave Studio. The Gamma shape monopole is derived by modification from the original T shaped monopole and the first three resonant frequencies are found to be well improved than the T shaped one. The typical frequencies at 789.5 MHz, 988.1 MHz, 2.088 GHz and 2.376 GHz are having peak gain of 2.94 dBi, 2.11 dBi, 5.81 dBi, 4.84 dBi and radiation efficiencies of 95.57 %, 87.32 %, 96.67 % and 95.36 %, respectively. Compared to the T shaped monopole antenna, the modified Gamma shaped monopole antenna is performing better for the first three resonant frequencies in terms of return loss. This work has achieved to accommodate the multiple frequency bands of GSM750, GSM850, GSM900, LTE800, LTE2300, PCS-1900 and UMTS. Proposed antenna size is 40 mm x 15 mm that is suitable to fit inside the commercially available tablet PCs.